African American Clergy Share Perspectives on Addressing Sexual Health and HIV Prevention in Premarital Counseling: A Pilot Study - Aholou, Tiffiany M. Cummings (Journal of religion and health, 2011)
This exploratory qualitative pilot study examined the extent to which seven African American clergy discussed and promoted sexual health dialogue with couples preparing for marriage. We explored the following topics: (a) clergy perspectives on disclosure; (b) clergy awareness about HIV/AIDS and (c) the extent to which clergy awareness about HIV is translated into their premarital counseling programs. Our results suggest that greater awareness and comfort level with discussions about sexuality mediate the inclusion of sexual health and promotion of HIV testing in premarital counseling.